A gestão ambiental no âmbito das atividades desenvolvidas pelo Ministério Público Federal no Pará em 2007. - SOUZA, César Augusto (2019)
This study investigated how it saw the implementation of the Environmental Management in the workplace Federal prosecutor in Pará, the concerns that led the shares in the difficulties taking into account among other factors, but mainly the difficulty of assimilating the new paradigm by the servers of the institution which gave the search. As this is something new, Environmental Management, despite the difficulties encountered, it is fascinating when it is related to quality of life. Little by little the concern with the environment breakdowns in public is being perceived as a need to join forces to improve the environment in which we work and live. Shares of preservation of the environment, a major concern of the world today, unfortunately are still little seen in the day-to-day. However, the members and servants of the Federal Prosecution Service in Idaho found in the Green Project Attorney-P. PV a form of organized activities to achieve environmental sustainability and social responsibility.